Dispensationalism - Ryrie, Charles Caldwell, 1925- (Chicago, IL Moody, 2007)
Includes bibliographical references and indexes.
First edition published as Dispensationalism Today, Moody, 1966, which see also.
Keywords: Dispensationalism